Cases of feminicide in Caazapá during 2022 to 2023: Analysis of the implementatn of the Latin American Model Protocol for the investigation of gender-related violent deaths of women (Legal journal - Research in Legal and Social Sciences, 2024)
A critical analysis of the Latin American Protocol for the Investigation of Violent Deaths of Women for Gender-Based Reasons is presented, with the general objective of examining its implementation in the Paraguayan criminal justice system in the department of Caazapá during 2022 and 2023. The study aimed to identify ways to adapt the guidelines, the regulatory and procedural challenges to effective implementation, and propose alternatives and/or adjustments to existing legislation to optimize its application.The methodology applied was qualitative, with a non-experimental design and a descriptive-projective scope. The findings reveal deficiencies in the adaptation of the Protocol, along with challenges such as the absence of detection measures, the need for a transversal public policy to foster collaboration among interested parties, and gaps in training, monitoring, and effective control of procedures. Other issues include the lack of accountability measures for prosecutors and judges whose actions contribute to impunity, insufficient structural and infrastructural resources, and the absence of state policies for victim support and protection. Additionally, biases and the minimization of these incidents further intensify the problem.The study concludes that beyond aligning Paraguayan procedural criminal law with the model established by the Protocol, there is an urgent need for social and cultural awareness towards a gender perspective that ensures equality and non-discrimination for women.
Keywords: Femicide Protocol; implementation; Latin America; Paraguay; Caazapa